Beyond the Classic Pattern: Radiologic Insights into the Diverse Presentations of PRES - Varshney, Sumedha; Namrata,; Rahul, Ranjan; Singh, Anil Kumar; Pandey, Nirmal; Gupta, Asheesh Kumar (Nepal Journal of Neuroscience, 2026)
Posterior reversible encephalopathy syndrome (PRES) is also called Reversible posterior leukoencephalopathy syndrome (RPLS). PRES typically manifests as parieto-occipital vasogenic edema, but radiologic investigations show a much wider range of involvement. Large studies have shown extension of the imaging findings in atypical areas and in atypical pattern. Also PRES has large number of etiological factors. Given its wide range of triggers, such as hypertension, renal failure, eclampsia, autoimmune illness, and cytotoxic treatments, prompt identification is crucial to enable prompt treatment of underlying causes and avoid irreparable damage or complications. Therefore, being aware of abnormal imaging patterns is essential for timely and efficient treatment and this article aims to review the imaging features of classical PRES and its variants.